The Relativistic Jet-accretion Flow-wind Connection in Mrk 231 - Reynolds, C.; Punsly, B.; Miniutti, G.; O'Dea, C.; Hurley-Walker, Natasha (Institute of Physics Publishing, 2017)
Long-term radio monitoring of the broad absorption line (BAL) quasar Mrk 231 at 17.6 GHz detected a strong flare in 2015. This triggered four epochs of Very Long Baseline Array (VLBA) observations from 8.4 to 43 GHz as well as three epochs of X-ray observations with NuSTAR and two with XMM over a 15 week period. Two ejected components were detected by the VLBA observations. A conservative lower bound on the apparent speed of the first ejection is attained by assuming that it was ejected when the flare began, v app > 3.15c. Serendipitous far-UV Hubble Space Telescope observations combined with our long-term radio monitoring seem to indicate that episodes of relativistic ejections suppress flux that is emitted at wavelengths shortward of the peak of the far-UV spectral energy distribution, similar to what has been observed in radio-loud quasars. Episodes of strong jet production also seem to suppress the high-ionization BAL wind seen in weak jet states. We found a statistically significant increase (~25%) of the 3-12 keV flux during the radio flare relative to a quiescent radio state. This is explained by an ultra-fast (~0.06c) X-ray-absorbing photoionized wind that is significantly detected only in the low-radio state (similar to Galactic black holes). Mrk 231 is becoming more radio loud. We found that the putative parsec-scale radio lobe doubled in brightness in nine years. Furthermore, large flares are more frequent, with three major flares occurring at ~2 year intervals.